Desain dan Analisis Pengukuran Viskositas dengan Metode Bola Jatuh Berbasis Sensor Optocoupler dan Sistem Akuisisinya pada Komputer - Warsito, Warsito; Suciyati, Sri Wahyu; Isworo, Dyan (Jurnal Natur Indonesia, 2012)
It has been designed and analyzed the low cost viscometer using falling ball method, the sample analyzed is glycerin fluid at 20oC. Two optocoupler circuits have been used as time measurement system of falling ball between two references point, light source used was infrared laser diode. The computer acquisition system use serial communication and it has been perfectly made and characterized. The velocity measurement system has 0.75 x 10-1 s resolution, but the resolution of integrated system both of hardware and acquisition software, is about 10-1 s. The theoretical viscosity value has been calculated and simulated to abtain the absolute viscosity value. This simulation results have been analyzed and compared with the experiment results. The correction factor for velocity calculation has been discussed and gave the optimum value of velocity correction factor (0.4425), regarding to the dimension of tube and ball used in this research. Based on the experiment, the viscosity of glycerin obtained was 1418.0309±1.6157 mPa.s., this value was with similar with the literatures and has a 0.57% of accuracy error (ε0).